The role of IL-1 in the induction of IL-17 producing T cells - Sutton, Caroline Eva (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2008)
T helper cell responses have traditionally been divided into two distinct subsets, Th1 and Th2, producing IFN-y and IL-4 respectively. However, more recently the IL-12 family member, IL-23, has been shown to have a role in the development of IL-17 producing T cells (T IL-17), including Th cells. The initial aim of this project was to examine the adjuvant activity of heat labile enterotoxin from Escherichia coli (LT). In the course of these studies, designed to examine the role of IL-1 in the adjuvant effect of LT, I discovered a novel role for IL-1 in the induction of T IL-17 cells.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin